A divergent synthetic approach to diverse molecular scaffolds: assessment of lead-likeness using LLAMA, an open-access computational tool. Issue 45 (5th May 2016) - Colomer, Ignacio; Empson, Christopher J.; Craven, Philip; Owen, Zachary; Doveston, Richard G.; Churcher, Ian; Marsden, Stephen P.; Nelson, Adam
Abstract : LLAMA was used to assess the lead-likeness of scaffolds prepared via complementary cyclisations of hex-2-ene-1, 6-diamine derivatives. Abstract : Complementary cyclisation reactions of hex-2-ene-1, 6-diamine derivatives were exploited in the synthesis of alternative molecular scaffolds. The value of the synthetic approach was analysed using LLAMA, an open-access computational tool for assessing the lead-likeness and novelty of molecular scaffolds.